Evaluation of Opioid Prescriptions After Urogynecologic Surgery Within a Large Health Care Organization: How Much Are We Prescribing?. Issue 2 (March 2019) - Buono, Kristen; Brueseke, Taylor; Wu, Jun; Whitcomb, Emily
Abstract : Objectives: Data regarding postoperative opioid prescriptions for patients undergoing urogynecologic surgery are sparse. Our objective was to quantify surgeon prescribing patterns for patients undergoing surgery for pelvic organ prolapse or stress urinary incontinence. Methods: Patients who underwent surgery for pelvic organ prolapse or SUI within a large health care maintenance organization were identified by procedural codes within the electronic medical record. Medical records were reviewed for demographic and clinical data. Our primary objective was to describe initial postoperative morphine milligram equivalent (MME) dosages for patients undergoing various urogynecologic surgeries. Secondary objectives were to evaluate rates of postoperative non-opioid analgesic prescriptions, presence of additional postoperative opioid prescriptions within 90 days of surgery, and to characterize prescribing patterns of surgeons from different specialties. Results: We evaluated 855 patients undergoing 7 urogynecologic surgeries. There was wide variation in the quantity of MME prescribed to patients undergoing different urogynecologic surgeries, and the mean MME ranged from 137.6 mg after a colpocleisis to 214.1 mg after a laparoscopic uterosacral ligament suspension. Less than two thirds of patients received a postoperative nonsteroidal anti-inflammatory drug (NSAID) prescription, and rates of NSAID prescriptions varied widely between surgeons from different specialties. Thirty-nine (4.6%) patients received an additional postoperative opioid prescription specifically for the indication of persistent postoperative pain. Conclusions: There is wide variation in the range of MME prescribed postoperatively to patients undergoing common urogynecologic surgeries. Less than two thirds of patients received a postoperative NSAID prescription, which was found to be independently associated with a higher postoperative opioid prescription dose.